The Marriage Family Assimilation Between Women of Toba Batak Ethnics and Men of Tionghoa Ethnics in Doloksanggul, North Sumatra - Rita Lumban Gaol (Program Studi Antropologi Sosial Pascasarjana Universitas Negeri Medan, 2018)
The purposes of this study are to analyze; (1) the process of mixed marriages or assimilation between the marriages of Toba Batak women and Tionghoa Men in Doloksanggul. (2) the important factors encouraging mixed marriages between Batak Toba women and Tionghoa men in Doloksanggul, and (3) the mixed marriages harmony between Toba Batak women and Tionghoa Men in Doloksanggul. This research is qualitative method. The results of this study are; cultural assimilation: the process of adopting values, beliefs, dogmas, language ideologies and symbol systems of an ethnic group or various groups for the formation of values, beliefs, dogmas, language ideology and symbolic systems of a new ethnic groups. Structural assimilation: the process of penetrating the culture of ethnic groups into other ethnic cultures through primary groups such as family, close friends. In the marriage assimilation, or often called physical assimilation that occurs because of inter-ethnic or inter-racial marriages, produces a new ethnicities or races, which have different cultures, there is an association among individuals or groups intensively and in a relatively long time. People from different cultural backgrounds, interacting directly intensively for a long time which changed their form into elements of mixed culture. Usually, the groups involved in an assimilation process are a majority group and some minority groups that change the specific characteristics of their cultural elements and adapt them to the culture of the majority, so that gradually they lose their cultural personality and produce the majority culture. The conclusion of this field research is that; the interaction between ethnic Tionghoa and Toba Batak in Doloksanggul expressing a pattern of adaptation in an associative social process. The interaction is carried out in the form of accommodation and cooperation and acculturation. The pattern of interaction carried out by Tionghoa ethnic is as their effort to be a part of participating as Doloksanggul community members. Although the adjustment referred to is still more economic in nature, anthropologically it can be seen as a part of the social process towards social harmony and social integration